PENGARUH KELEKATAN DAN HARGA DIRI TERHADAP KEMAMPUAN BERSOSIALISASI ANAK - NORA, MAYA OKTIA (Jurnal Pendidikan Usia Dini, 2015)
Abstract:This research was effected by the lack of ability to socialize at the grade 3 elementary school children in district of lubukalung. Lack of ability to socialize the child disebabkna by a lack of stimulation and parents not to give children a chance to interact with the crowd. Parents restrict children make friends with anyone, so in they can't interact well with her friends. This research aims to know the influence of attachment and self esteem against the ability of socializing children. Variables used in this study is the Attachment (X 1), self-esteem (X 2) and the ability to socialize (X 3). This research uses a quantitative approach, survey methods and techniques of path analysis. This research was conducted on class III SD in district of LubukAlung in May until June 2015. The technique used is the sample withdrawal multi sampling stages. The sample in this study 50 children. The results showed that attachment effect is positive towards the ability of socializing children, self-esteem effect directly against the ability of socializing children and togetherness, a positive effect against the child's self-esteem. Key Words:Attachment, Self-Esteem And The Ability To Socialize